Photoreceptor density in relation to axial length and retinal location in human eyes - Panda-Jonas, Songhomitra; Jonas, Jost B.; Jonas, Rahul A. (Scientific reports, 2022)
The purpose of the study was to examine the density of retinal photoreceptors and retinal pigment epithelium (RPE) cells in relation to myopic axial elongation in human eyes. Using light microscopy, we assessed the density of photoreceptors and RPE cells at the ora serrata, equator, and midperiphery (equator/posterior pole midpoint), and the RPE cell density additionally at the posterior pole, in enucleated human globes. The study included 78 eyes (mean age: 59.2 ± 15.6 years; range: 32-85 years) with a mean axial length of 27.3 ± 3.6 mm (range: 21.5-37.0 mm). Close to the ora serrata, at the equator and midperiphery, photoreceptor and RPE cell density was 246 ± 183, 605 ± 299 and 1089 ± 441 photoreceptors/mm and 56.1 ± 13.7, 45.2 ± 15.1, and 48.8 ± 15.6 RPE cells/mm, respectively. Densities of both cell types in all three regions were positively correlated with each other (all P < 0.001) and decreased with longer axial length (all P < 0.001) and longer distance between the ora serrata and the posterior pole (all P < 0.001), most marked at the midperiphery and least marked close to the ora serrata. The PRE cell density at the posterior pole was not significantly (P = 0.35) related to axial length. The photoreceptor density at the ora serrata (beta:− 0.33) and equator (beta: − 0.27) and RPE cell density at the ora serrata (beta: − 0.27) decreased additionally with the presence of glaucoma. The findings suggest that the axial elongation-related decrease in photoreceptor and RPE cell density is most marked at the midperiphery, followed by the equator and finally the ora serrata region. It suggests that the axial elongation-related enlargement of the eye wall predominantly takes place in the retro-equatorial region, followed by the equatorial region.
Gesehen am 19.01.2024